Behavior and lineage progression of neural progenitors in the mammalian cortex. (February 2021) - Lin, Yang; Yang, Jiajun; Shen, Zhongfu; Ma, Jian; Simons, Benjamin D; Shi, Song-Hai
Abstract : The cerebral cortex is a central structure in the mammalian brain that enables higher cognitive functions and intellectual skills. It is the hallmark of the mammalian nervous system with enormous complexity, consisting of a large number of neurons and glia that are diverse in morphology, molecular expression, biophysical properties, circuit connectivity and physiological function. Cortical neurons and glia are generated by neural progenitor cells during development. Ensuring the correct cell cycle kinetics, fate behavior and lineage progression of neural progenitor cells is essential to determine the number and types of neurons and glia in the cerebral cortex, which together constitute neural circuits for brain function. In this review, we discuss recent findings on mammalian cortical progenitor cell types and their lineage behaviors in generating neurons and glia, cortical evolution and expansion, and advances in brain organoid technology that allow the modeling of human cortical development under normal and disease conditions.